DNMT3a in the hippocampal CA1 is crucial in the acquisition of morphine self‐administration in rats. (5th April 2019) - Zhang, Jian‐Jun; Jiang, Feng‐Ze; Zheng, Wei; Duan, Ying; Jin, Shu‐Bo; Shen, Fang; Liang, Jing; Li, Ming; Sui, Nan
Abstract: Drug‐reinforced excessive operant responding is one fundamental feature of long‐lasting addiction‐like behaviors and relapse in animals. However, the transcriptional regulatory mechanisms responsible for the persistent drug‐specific (not natural rewards) operant behavior are not entirely clear. In this study, we demonstrate a key role for one of the de novo DNA methyltransferase, DNMT3a, in the acquisition of morphine self‐administration (SA) in rats. The expression of DNMT3a in the hippocampal CA1 region but not in the nucleus accumbens shell was significantly up‐regulated after 1‐ and 7‐day morphine SA (0.3 mg/kg/infusion) but not after the yoked morphine injection. On the other hand, saccharin SA did not affect the expression of DNMT3a or DNMT3b. DNMT inhibitor 5‐aza‐2‐deoxycytidine (5‐aza) microinjected into the hippocampal CA1 significantly attenuated the acquisition of morphine SA. Knockdown of DNMT3a also impaired the ability to acquire the morphine SA. Overall, these findings suggest that DNMT3a in the hippocampus plays an important role in the acquisition of morphine SA and may be a valid target to prevent the development of morphine addiction. Abstract : The expression of DNMT3a was up‐regulated in the hippocampal CA1, not in the NAc shell, after the morphine self‐administration (SA), but not after the yoked morphine injection or saccharin SA. DNMTs inhibitor 5‐aza‐2‐deoxycytidine microinjected into the CA1 or knockdown of DNMT3a in the CA1 attenuated the acquisition of morphine SA. These findings indicate that DNMT3a in the CA1 could potentially be a target for preventing the development of opioids addiction.